2012
DOI: 10.1103/physrevlett.109.247203
|View full text |Cite
|
Sign up to set email alerts
|

Strong Paramagnetism of Gold Nanoparticles Deposited on aSulfolobus acidocaldariusSLayer

Abstract: Magnetic properties of Au nanoparticles deposited on an archaeal S layer are reported. X-ray magnetic circular dichroism and superconducting quantum interference device magnetometries demonstrate that the particles are strongly paramagnetic, without any indication of magnetic blocking down to 16 mK. The average magnetic moment per particle is M part ¼ 2:36ð7Þ B . This contribution originates at the particle's Au 5d band, in which an increased number of holes with respect to the bulk value is observed. The magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…1,5 New complexity has been introduced by the observation of ferromagnetism in undoped semiconductor thin lms and nanostructures. 13,14 Among them, magnetism in ZnO has also been studied more than that of any other compound or semiconductor. [7][8][9] Venkatesan et al 6 have observed d 0 magnetism in HfO 2 thin lms and have triggered extensive experimental activities in the eld of the room-temperature ferromagnetism of many semiconductors and nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 New complexity has been introduced by the observation of ferromagnetism in undoped semiconductor thin lms and nanostructures. 13,14 Among them, magnetism in ZnO has also been studied more than that of any other compound or semiconductor. [7][8][9] Venkatesan et al 6 have observed d 0 magnetism in HfO 2 thin lms and have triggered extensive experimental activities in the eld of the room-temperature ferromagnetism of many semiconductors and nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.1103/PhysRevLett.111.127202 PACS numbers: 75.75.Àc, 73.22.Àf, 75.20.En, 78.67.Qa Bulk Au is a diamagnetic material, i.e., one with a negative volume magnetic susceptibility Au . Recently, it was reported that Au nanoparticles (NPs), with functionalized surfaces, show a broad range of magnetic behavior, ranging from (enhanced) diamagnetic [1,2] to (super)paramagnetic [3][4][5] and even ferromagnetic up to room temperature [6,7]. The NP size and the type of capping molecules, strongly binding to or weakly interacting with Au, appear to influence the magnetic response.…”
mentioning
confidence: 99%
“…The NP size and the type of capping molecules, strongly binding to or weakly interacting with Au, appear to influence the magnetic response. Several explanations were suggested, such as competing magnetic contributions of the NP core and surface [3], the formation of a magnetic moment due to the exchange of charges at the Au-ligand interface [5,6,8], the creation of large orbital moments due to electron motion within surface clusters [9], and the occurrence of persistent currents in the Au core [2]. However, so far, the origin of this unexpected magnetism and why it differs strongly between different types of NPs is not yet understood [2,10,11].…”
mentioning
confidence: 99%
“…So far the author is concerned, there are not, in the literature, magnetic moment measurements for gas phase Au 2 . Nevertheless, a magnetic moment of 2.36 BM per particle was reported [6] for deposited gold nanoparticles. It was verified that the magnetic contribution originates at the particle's Au 5d band [6].…”
Section: Resultsmentioning
confidence: 99%
“…The SE-PM6 approach was chose taking into account its minor computation time consuming and its reliability, as verified for PtF 6 [3]. The calculated values 4 were compared with the experimental value obtained by means of Knudsen effusion mass spectrometric studies [5].…”
Section: Methodsmentioning
confidence: 99%